Overlapping school and farming calendars in Madagascar: Simulating gains of alternative school calendars - Allen IV, James (International Food Policy Research Institute, 2024)
This report summarizes ongoing analysis of overlap between school and farming calendars in Madagascar in collaboration with the World Bank office in Madagascar. Following IFPRI Discussion Paper 2235 (Allen 2024), I develop a community-based measure of overlap as the number of days that the school calendar overlaps with crop calendars that weights the relevance of each crop by the community crop share and then aggregates across crops. A policy simulation of alternative school calendars identifies early January as the best time to start Madagascar's national school calendar (assuming the same structure as the actual school calendar) to avoid overlap with peak farming periods. Further, it finds additional gains can be made to reducing overlap by decentralizing school calendars to the local level and adopting each community's overlap-minimizing calendar. Next steps in 2025 include an empirical analysis that estimates the correlation between overlap and key education outcomes that simulates the potential gains of a locally decentralized overlap-minimizing school calendar.